Multimycotoxin Analysisin Grains by UHPLC-MS/MS - Bogantes Ledezma, Diego (2025)
Mycotoxins are toxic fungal metabolites that pose significant food safety risks and cause substantial economic losses. Due to their widespread occurrence, regulatory limits vary across countries. Multimycotoxin analysis in diverse food matrices remains challenging due to their distinct chemical properties. This document presents a validated, cost-effective protocol for extracting and analyzing nine major mycotoxins (aflatoxins B1, B2, G1 and G2, deoxynivalenol, fumonisin B1, ochratoxin A, T–2 toxin and zearalenone) in common beans, groundnuts, maize, rice and wheat by means of ultra-high performance liquid chromatography (UHPLC) equipment coupled to tandem mass spectrometry (MS/MS) with triple quadrupole. The method reduces costs by minimizing organic solvent use, replacing acetonitrile with methanol, and eliminating immunoaffinity or solid-phase columns. Additionally, it is time-efficient and environmentally friendly. This protocol provides a practical and sustainable approach to multimycotoxin detection, improving food safety monitoring.